2-Methoxyestradiol protects against IgG immune complex-induced acute lung injury by blocking NF-κB and CCAAT/enhancer-binding protein β activities. (May 2017) - Yan, Chunguang; Shen, Yanfei; Sun, Qiqing; Yuan, Dong; Tang, Huifang; Gao, Hongwei
Highlights: 2ME2 inhibits IgG IC-induced acute lung injury. 2ME2 blocks NF-κB and C/EBPβ activation in IgG IC-treated macrophages. 2ME2 reduces p38 MAPK and ERK1/2 activities in macrophages challenged by IgG IC. The MAPKs positively regulate C/EBPβ expression in macrophages treated with IgG IC. Abstract: Increasing evidences indicate that 2-Methoxyestradiol (2ME2) plays an essential role in protecting against inflammatory responses. However, its effect on IgG immune complex (IC)-induced acute lung injury (ALI) remains enigmatic. In the study, by using i.p. administration of 2ME2, we evaluated its influence on IgG IC-induced pulmonary injury in mice. We found that during IgG IC-induced ALI, mice treated by 2ME2 displayed a substantial decrease in vascular permeability and neutrophil influx (represented by myeloperoxidase activity) when compared with their counterparts receiving vehicle treatment. Furthermore, 2ME2 treatment significantly decreased pro-inflammatory mediator production and inflammatory cell, especially neutrophil accumulation in bronchoalveolar lavage fluids (BALFs) upon IgG IC stimulation. In vitro, IgG IC-triggered inflammatory mediator production was markedly down-regulated by 2ME2 in macrophages. Moreover, we verified that the activation of the transcription factors, NF-κB and CCAAT/enhancer-binding protein (C/EBP) β, were inhibited by 2ME2 in IgG IC-challenged macrophages. We demonstrated that alleviation of NF-κB-dependent transcription might be associated with reduced phosphorylation of NF-κB p65, and reduction of C/EBP activation was directly linked to its expression. In addition, we discovered that IgG IC-stimulated phosphorylation of both p38 MAPK and ERK1/2 was alleviated by 2ME2. These data indicated a novel strategy for blockade of IgG IC-induced inflammatory activities.